An analysis of the labour turnover situation in First Allied Savings and Loans Limited; its impact and the way forward. - Asah-Adu, Rosemary (2011)
A thesis submitted to the College of Arts and Social Sciences in partial fulfilment of the requirements for the award of Master of Arts (Economics),